2017
DOI: 10.1016/j.jet.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The pricing effects of ambiguous private information

Abstract: Ambiguous private information leads to informational inefficiency of market prices in rational expectations equilibrium. This inefficiency implies lower asset prices as uninformed traders require a premium to hold assets. This premium is increasing in the riskiness of the asset and leads to excess volatility, price swings, and abrupt volatility and illiquidity variation across informational efficiency regimes. Public information affects the informational efficiency of price and can also lead to abrupt changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Several recent models have shown that ambiguity aversion may lead to forms of portfolio inertia in that households may wish to keep their risk exposure constant over time even upon observing shocks, say, to the distribution of expected returns. Portfolio inertia can have important consequences also for the functioning of asset markets, as it impacts the amount of information revealed in prices and ultimately their level and volatility (Condie and Ganguli (2012)).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several recent models have shown that ambiguity aversion may lead to forms of portfolio inertia in that households may wish to keep their risk exposure constant over time even upon observing shocks, say, to the distribution of expected returns. Portfolio inertia can have important consequences also for the functioning of asset markets, as it impacts the amount of information revealed in prices and ultimately their level and volatility (Condie and Ganguli (2012)).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…6 Our work is also related to a large literature on the informational efficiency of prices in the presence of asymmetric information. For instance, prices do not fully reveal private information in equilibrium (i) if it is costly to acquire information (Grossman (1976), Grossman and Stiglitz (1976)), (ii) if there are noise traders (Grossman and Stiglitz (1980)), (iii) if informed investors anticipate how their trades will impact prices (Kyle (1985), Back, Cao, and Willard (2000)), and (iv) if there is ambiguity (Caskey (2009), Condie and Ganguli (2017)). What is striking in this paper is that a costless informative public signal is not always incorporated into the price (i.e., the price is not a sufficient statistic for the signal) when an investor is averse to ambiguity in the workhorse learning models in finance.…”
mentioning
confidence: 99%
“…The disagreement creates a dispersed bid and offer price among investors and drives high trading price volatility (Ma, Wang, Cheng, & Hu, 2017). Disagreement among investor come from different quality of private information among investors and the quality of their interpretation of public information (Condie & Ganguli, 2017). If there is a dominant player in the market, for example, dealer order flows are very high, but on the other hand, customer order flows are trivial, the disagreement would have low price impact.…”
Section: Buddi Wibowomentioning
confidence: 99%